Philosophical Issues of Nanotechnologies: Ontological-Systemic Starting Points and Ethical Implications - Bartoš, Vít; Trčka, Michal (Teorie vědy / Theory of Science, 2023)
From the perspective of philosophy of science and technologies, we firstly attend to the issue of the role of nanotechnologies within the evolution of technologies. We recognize their utmost importance in the respect that they are technologies of life itself. We further explain that the nano-level is the domain of intersection of the rules of quantum physics and traditional Newtonian physics. This is our starting point from which we discuss the issue of conditions under which minimizing things also changes their functional essence. We use the example of the Drexler vs. Smalley debate to demonstrate the paradigmatic incomparability of the two perspectives and the physical-chemical and engineering-related limits of nanotechnologies. We discuss to what extent are the dangers and ethical implications emerging from Drexler’s contemplations real, be it what he calls the “grey goo” problem or the issues of molecular production. We regard certain problems linked to synthetic biology as more serious. We conclude our text with the consideration that the human civilization should think of the possibilities of nanotechnologies in the development of life as an existential challenge.